2015
DOI: 10.1002/cjp2.10
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of MYC translocation positive diffuse large B‐cell lymphoma depends on the second hit

Abstract: A proportion of MYC translocation positive diffuse large B‐cell lymphomas (DLBCL) harbour a BCL2 and/or BCL6 translocation, known as double‐hit DLBCL, and are clinically aggressive. It is unknown whether there are other genetic abnormalities that cooperate with MYC translocation and form double‐hit DLBCL, and whether there is a difference in clinical outcome between the double‐hit DLBCL and those with an isolated MYC translocation. We investigated TP53 gene mutations along with BCL2 and BCL6 translocations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 36 publications
3
44
0
1
Order By: Relevance
“…Studies have shown that TP53 mutation is associated with P53 overexpression and both are associated with an inferior prognosis in patients with diffuse large B-cell lymphoma [37][38][39]. Previous studies have shown that P53 expression can enhance the negative effect of MYC translocation and expression [40,41]. In earlier studies, P53 overexpression was shown to augment the negative prognostic effect of MYC/BCL2 double hit lymphoma and MYC/BCL2 double expression lymphoma [28,30]; in other words, P53 expression is a poor prognostic factor in MYC/BCL2 double hit lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that TP53 mutation is associated with P53 overexpression and both are associated with an inferior prognosis in patients with diffuse large B-cell lymphoma [37][38][39]. Previous studies have shown that P53 expression can enhance the negative effect of MYC translocation and expression [40,41]. In earlier studies, P53 overexpression was shown to augment the negative prognostic effect of MYC/BCL2 double hit lymphoma and MYC/BCL2 double expression lymphoma [28,30]; in other words, P53 expression is a poor prognostic factor in MYC/BCL2 double hit lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…The authors postulate that in this setting, TP53 mutations may be synergistic with BCL2 translocations through inhibition of apoptosis, and furthermore, the combination may confer a competitive advantage in clonal evolution. Interestingly, Clipson et al 49 noted that patients with DLBCL with MYC rearrangements and TP53 mutations demonstrated worse survival than patients with MYC/BCL2 DHL, and this suggested the need to evaluate for TP53 mutations in cases of MYC-rearranged DLBCL. Wang et al 11 also evaluated the impact of p53 expression in MYC-rearranged DLBCL, MYC-overexpressed DLBCL, MYC/BCL2 DHL, and DEL.…”
Section: Is the Specific Pattern Of Genomic Abnormalities Important Imentioning
confidence: 99%
“…(5)(6)(7)(8) In over half of the cases, MYC rearrangements occur in combination with a second hit in the BCL2 and/or BCL6 genes and these patients demonstrate an even worse outcome with a median overall survival (OS) reported between 0.2 and 1.5 years. (5,(8)(9)(10)(11)(12) In the 2017 revision of the WHO c double hit lymphomas (or triple hit lymphomas ) are classified as a separate disease entity with a very aggressive behavior. (13) In addition, 19 to 34% of the DLBCL patients have double protein expression of MYC and BCL2 (DE), but lack genetic rearrangements in these genes, demonstrating an intermediate survival between DLBCL with single or no expression of MYC and BCL2, and DLBCL with double or triple hits.…”
Section: Introductionmentioning
confidence: 99%